2022
DOI: 10.13057/asianjfor/r060203
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of carbon stock and emission of community forests in Eastern Amhara, Ethiopia

ABEBE BIADGLIGNE,
TSEGAYE GOBEZIE,
ABEBE MOHAMMED
et al.

Abstract: Abstract. Biadgligne A, Gobezie T, Mohammed A, Feleke E. 2022. Estimation of carbon stock and emission of community forests in Eastern Amhara, Ethiopia. Asian J For 6: 74-82. Carbon emission resulting from deforestation and forest degradation contributes to climate change. Halting deforestation is, therefore, one strategy to mitigate the changing climate. As the global carbon market develops, an opportunity to halt deforestation can be contributed by community forests as a win-win solution for climate change m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 41 publications
0
4
2
Order By: Relevance
“…The mean above-ground biomass and potential carbon stocks of the forest reserve for trees and shrubs with diameter ≥5cm were 116.19±70.61 Mg ha -1 and 56.93±34.60 Mg C ha -1 respectively, while the mean below-ground biomass and potential carbon stocks of the forest reserve for trees and shrubs with diameter ≥5cm were 70.84±40.24 Mg ha -1 and 34.71±19.72 Mg C ha -1 , respectively (Table 1, Figure 6). Tree species which had high contribution to the observed above-ground carbon density were C. malosana (11.74±3.85 Mg C ha -1 ), D. natalensis (10.12±4.60 Mg C ha -1 ), D. abyssinica (6.50±2.73 Mg C ha In contrast, the total mean aboveground carbon stocks found in this study is higher than that reported by Mwaluseke (2015) from a dry evergreen forest of Lendikinya Forest Reserve in Tanzania who reported a value of 16.04±7.7 t C ha -1 ; Biadgligne et al (2022) reported two values of 14.84±1.27 t C ha -1 and 3.49±0.66 t C ha -1 from two community forests from Ethiopia; Solomon et al (2017) The high value reported by several authors could be due to differences in climatic conditions of these sites in terms of rainfall received and the presence of many large trees which had significant contribution to the total mean carbon density than the presence of many small trees reported in this study (Mauya and Madundo 2021). According to Mauya and Madundo (2021) climate, topography as well as estimation methods particularly the selection of allometric models is also key factors when it comes to accurate estimation of AGB and AGC in the different study sites.…”
Section: Biomass and Carbon Storagecontrasting
confidence: 80%
See 3 more Smart Citations
“…The mean above-ground biomass and potential carbon stocks of the forest reserve for trees and shrubs with diameter ≥5cm were 116.19±70.61 Mg ha -1 and 56.93±34.60 Mg C ha -1 respectively, while the mean below-ground biomass and potential carbon stocks of the forest reserve for trees and shrubs with diameter ≥5cm were 70.84±40.24 Mg ha -1 and 34.71±19.72 Mg C ha -1 , respectively (Table 1, Figure 6). Tree species which had high contribution to the observed above-ground carbon density were C. malosana (11.74±3.85 Mg C ha -1 ), D. natalensis (10.12±4.60 Mg C ha -1 ), D. abyssinica (6.50±2.73 Mg C ha In contrast, the total mean aboveground carbon stocks found in this study is higher than that reported by Mwaluseke (2015) from a dry evergreen forest of Lendikinya Forest Reserve in Tanzania who reported a value of 16.04±7.7 t C ha -1 ; Biadgligne et al (2022) reported two values of 14.84±1.27 t C ha -1 and 3.49±0.66 t C ha -1 from two community forests from Ethiopia; Solomon et al (2017) The high value reported by several authors could be due to differences in climatic conditions of these sites in terms of rainfall received and the presence of many large trees which had significant contribution to the total mean carbon density than the presence of many small trees reported in this study (Mauya and Madundo 2021). According to Mauya and Madundo (2021) climate, topography as well as estimation methods particularly the selection of allometric models is also key factors when it comes to accurate estimation of AGB and AGC in the different study sites.…”
Section: Biomass and Carbon Storagecontrasting
confidence: 80%
“…The role of forest ecosystems in the conservation of soil, water and biodiversity and in mitigating climate change is well acknowledged (Burgess et al 2007;Pan et al 2011;Lewis et al 2013;Ashagre et al 2014;Spracklen and Righelato 2014;Apguaua et al 2015;Kacholi et al 2015;Mauya et al 2019;Kendie et al 2021;Biadgligne et al 2022;Nugroho et al 2022;Rawal and Subedi 2022). Forests contain most of the terrestrial biodiversity and are estimated to store about 289 Gt of biomass carbon (Apguaua et al 2015;FAO 2022).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, it can be used as a basis for buying and selling carbon stocks (Komul et al, 2016). According to Biadgligne (2022), the increasing interest in carbon trading today can provide opportunities for better forest management. This can be used as a solution for mitigating climate change and providing livelihoods for forest-based communities.…”
Section: Introductionmentioning
confidence: 99%